The role of polymorphic HLA-DR beta chain residues in presentation of viral antigens to T cells (The Rockefeller University Press, 1990)
The relative importance of 11 polymorphic positions in the HLA-DR7 beta 1 chain in T cell recognition of foreign antigens was investigated using transfectants expressing mutant DR7 beta 1 chains as APC for five rabies virus-specific T cell clones. The results indicate that multiple amino acids, located in both the beta-strands and alpha-helix of DR7 beta 1 in the model of a class II molecule, are involved in DR7- restricted T cell recognition of these antigens. Many of the substitutions appeared to reduce the affinity of an antigenic peptide for the mutant DR7 molecules but did not prevent binding. The heterogeneity of responses of the three G-specific T cell clones to presentation of the G11.3 peptide by several of the mutant DR7 molecules indicates that the T cell receptor (TCR) of each these clones requires a different view of the G11.3/DR7 complex and raises the possibility that the G11.3 peptide may bind to the DR7 molecule in more than one conformation.